PCR technique for detecting Toxoplasma gondii in animal amniotic fluid - Jitbanjong Toomphong Wiengcharoen (2018)
The goal of diagnosing congenital toxoplasmosis is early detection of maternofetal transmission, for early treatment to prevent unwanted sequelae. Polymerase chain reaction (PCR) is a method used recently for detecting toxoplasmosis during pregnancy. Amniotic fluid is a the clinical specimen used, since it provides a rapid, simple and safe method to obtain accurate results. The advantages of the PCR technique are high sensitivity, specificity and positive predictive value compared with other laboratory methods. To determine the sensitivity, specificity and lower detection limits in our laboratory, amplification of the B1 gene by nested PCR was performed on Toxoplasma gondii tachyzoites added to animal amniotic fluid samples. From 48 samples, our technique detected T.gondii in 30 out of 41 positive samples, and gave negative results for all the negative samples. The sensitivity for this nested PCR was 73%, the specificity was 100%, and the efficiency of the test was 77.1%. The nested PCR technique is recommended as a diagnostic method for detecting T.gondii in suspected congenital toxoplasmosis animals.